Efficacy and perceived challenges in implementing psychological interventions in palliative care: a scoping review: 10.55131/jphd/2025/230322 - S B, Keerthana; A, Kubendran (Journal of Public Health and Development, 2025)
Ensuring the well-being of terminally ill individuals’ mental health is just as crucial as their physical health. This review examines the perceived challenges and efficacy of providing psychological interventions to individuals receiving palliative care. This comprehensive literature review was conducted based on both Arksey and O’Malley’s and Joanna Briggs Institute (JBI) guidelines. The article was searched between March 2024 and June 2024 using several electronic databases such as Scopus, PubMed, and Web of Science. The applied inclusion criteria were articles published in English from 2005 to 2023, and studies conducted specifically in palliative care settings. PRISMA guidelines for scoping reviews were used for the selection process. After screening based on objective and specific inclusion criteria, 21 articles were chosen for extensive study of their full texts. The key themes derived from the review are the ‘psychological interventions and their implementation efficacy, mental health issues in palliative care, and challenges in implementing psychological interventions’. Patients receiving palliative care have experienced various psychological distresses, although these concerns are inadequately addressed and treated by healthcare providers. Psychological interventions are feasible and applicable in palliative care but their implementation efficacy is limited. The main challenges encountered include a lack of information, inadequate training and supervision, a well-defined role and framework for administering psychological care, and resources for implementing psychological interventions. This review highlights the existing challenges and the crucial implementation of a framework for effectively integrating psychological interventions alongside physical care. These challenges should be addressed in future research, and large-scale studies should be conducted to investigate the effects of psychological interventions.